PENGARUH MEDIA LKS BERBASIS MODEL TAKE AND GIVE TERHADAP HASIL BELAJAR IPA SISWA KELAS V SD NEGERI JABUNG 01 KEC.JABUNG KAB.MALANG - Prabawati, Rizky Nadya; Yayuk, Erna; Kuncahyono, Kuncahyono (Program Studi Pendidikan Guru Sekolah Dasar Universi, 2017)
Abstract: The existence of students’ Natural Science worksheets use as a media for doing exercises and being sources all at once. Uneffective tool of study for users, because of an incomplete material in students worksheets. This research aims to discover the impact of students worksheet media with take and give basis to natural science study results on fifth grade students in SD Negeri 1 Jabung, Jabung subdistrict Malang regency, and the total amount of the effect using students worksheet with take and give based model. This study used quantitative research approach and the type of this study was experimental study with true experimental design. The sample collection technique was simple random sampling. As a data population, the researcher choosen V grades students of SDN 1 Jabung , Jabung subdistrict, Malang regency with academic year of 2016/2017 amounted to 44 students. As an experimental class, the researcher choosen VB class as much as 23 students and VA class as a control class with the total students as much as 21 students. The result of the study shown that (1) in the hypothesis test which use t-test, the result is 0.032 with the significance 5%. It can be seen that the significant value (2-tailed) ˂ 0,05 means that Ho is rejected and Ha is accepted. (2) the total amount of the effect using students worksheet with take and give based model toward the result of IPA (Natural Science) study had a significant influece as much as 47,9%.Keywords: Effect, student worksheet, Take and Give, IPA (Natural Science) study resultAbstrak: Keberadaan LKS IPA digunakan sebagai media untuk mengerjakan soal sekaligus sebagai sumber belajar. Penggunaannya masih belum efektif sebagai sarana pembelajaran, karena materi yang terdapat dalam LKS dirasa belum lengkap. Penelitian ini bertujuan untuk mengetahui pengaruh media LKS berbasis model take and give terhadap hasil belajar IPA siswa kelas V SD Negeri Jabung 1 Kec.Jabung Kab.Malang, dan besar pengaruh penggunaan media LKS berbasis model take and give. Penelitian ini menggunakan pendekatan penelitian kuantitatif dan jenis penelitian eksperimen dengan desain true experimental design. Teknik pengambilan sampel menggunakan simple random sampling . Sebagai populasi data, dipilih siswa kelas V SD Negeri Jabung 1 Kec.Jabung Kab.Malang tahun ajaran 2016/2017 yang berjumlah 44. Yang terpilih menjadi kelas eksperimen yaitu kelas VB dengan jumlah 23 siswa dan kelas kontrol yaitu kelas VA dengan jumlah 21 siswa. Hasil penelitian menunujukkan (1) pada uji hipotesis yang menggunakan uji t, hasilnya sebesar 0,032 dengan taraf signifikan 5%. Terlihat bahwa nilai Sig.(2-tailed) < 0,05 sehingga Ho ditolak dan Ha diterima. (2) besar pengaruh penggunaan LKS berbasis model take and give terhadap hasil belajar IPA memberikan kontribusi sebesar 47,9% .Kata Kunci: Pengaruh, Lembar Kerja Siswa (LKS), Take and Give, Hasil Belajar IPA